The Algorithmic Sanctuary: Social-Interaction Burnout, Loneliness, and Emotional Attachment to AI Companions Among Young Adults in Indonesia - Ni Made Nova Indriani; Immanuel Simbolon; Sophia Lucille Rodriguez (HM Publisher, 2026)
Background: Post-pandemic digital life has produced a new affective phenomenon: large-language-model “AI companions” that invite two-way parasocial relationships. Counter-intuitively, the most intense users in urban Indonesia appear to be not the physically isolated but socially active young adults experiencing interaction burnout, who treat AI as a refuge from the judgment costs of a collectivist culture. Yet no integrated model has tested why relational strain translates into machine attachment in a Global-South setting. Objective: To examine whether social-interaction burnout and subjective loneliness predict emotional attachment to AI companions, whether AI parasocial interaction mediates the burnout-attachment path, and whether collectivist judgment apprehension moderates the loneliness-attachment link. Methods: Drawing on Parasocial Interaction Theory, the Computers-Are-Social-Actors paradigm, and emotional-labor theory, this cross-sectional survey of 1,200 young adults recruited through a public organization in Palembang, South Sumatera, Indonesia, measured social-interaction burnout, subjective loneliness, collectivist judgment apprehension, AI parasocial interaction, and emotional attachment to AI using validated Likert scales analysed with reliability, correlation, multiple regression, bootstrap mediation, and moderation. Results: All scales were reliable (α = 0.84–0.91; KMO = 0.96). The model explained 48% of variance in attachment (adjusted R² = 0.486, F = 284, p < 0.001). Parasocial interaction (β = 0.318), loneliness (β = 0.254), and burnout (β = 0.238) were the strongest predictors (all p < 0.001). Parasocial interaction partially mediated the burnout–attachment path (indirect = 0.160, 95% CI [0.132, 0.191]), and judgment apprehension moderated the loneliness–attachment link (β = 0.127, p < 0.001). Conclusion: Findings introduce the “Algorithmic Sanctuary” account of AI companionship and inform digital-wellbeing policy in collectivist societies.